THE INFLUENCE OF INFLUENCER MARKETING (X1), TIKTOK MEDIA EFFECTIVENESS (X2), AND BRAND AWARENESS (X3) ON PURCHASING DECISIONS AMONG GENERATION Z IN PONDOK KUBANG DISTRICT, CENTRAL BENGKULU REGENCY - Leo Afriza Saputra; Adi Sismanto (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2026)
Research on Generation Z in Pondok Kubang District, Central Bengkulu Regency, with the following problem formulation: What is the influence of Influencer Marketing (X1), TikTok Media Effectiveness (X2), and Brand Awareness (X3) on Purchasing Decisions among Generation Z in Pondok Kubang District, Central Bengkulu Regency? and The purpose of this study is to find out how Influencer Marketing (X1), the Effectiveness of Tiktok Media (X2) and Brand Awareness (X3) on Purchasing Decisions on Generation Z in Pondok Kubang District, Central Bengkulu Regency. The population used in this study is Generation Z in Pondok Kubang District, Central Bengkulu Regency, totaling 120 respondents. The sampling technique used accidental sampling based on predetermined criteria totaling 120 respondents. Data collection techniques were observation, documentation and questionnaires. The processed data were analyzed using the SPSS 24 formula. Based on the results of the research and analysis of the influence of the variables Influencer Marketing (X1), the Effectiveness of Tiktok Media (X2) and Brand Awareness (X3) on Purchasing Decisions on Tiktok Media on Generation Z in Pondok Kubang District, Central Bengkulu Regency. The following conclusions can be drawn: Influencer Marketing (X1) has a positive effect on consumer purchasing decisions (Y) on Tiktok Media in Generation Z in Pondok Kubang District, Central Bengkulu Regency. This is proven by the hypothesis test with t-test obtained tcount> ttable (3.494>1.980), Effectiveness of Tiktok Media (X2) has a positive effect on consumer purchasing decisions (Y) on Tiktok Media in Generation Z in Pondok Kubang District, Central Bengkulu Regency. This is proven by the hypothesis test with t-test obtained tcount> ttable (13.546>1.980), Brand Awareness (X2) has a positive effect on consumer purchasing decisions (Y) on Tiktok Media in Generation Z in Pondok Kubang District, Central Bengkulu Regency. This is proven by the hypothesis test with t-test obtained tcount> ttable (4.365>1.080), Influencer Marketing (X1), Effectiveness of Media TikTok (X2), Brand Awareness (X3), and Social Values (X4) influence consumer purchasing decisions (Y). This can be seen from the simultaneous hypothesis test: Ftable > Fcount (162.613 > 3.920). This is evidenced by the correlation analysis, R = 0.899 (89.9%), which is close to 1. The coefficient of determination is R2 = 0.808, or approximately 80.8%, with the remaining 19.2% contributed by other variables not examined. Keywords: Influencer Marketing, TikTok Media Effectiveness, Brand Awareness, Purchasing Decise